Humanities between Professional Ethics and Economic Claims (KULT_online, 2011)
The book Sind Geisteswissenschaften nützlich? Geisteswissenschaften im Diskurs der Marktfähigkeit (Are the Humanities Useful? Humanities in the Discourse of Marketability), written by Insa Gülzow, investigates how the knowledge of humanities might be combined with the domain of the economy. Even though Gülzow's aim is to provide a third way between a proclaimed usefulness and a programmatic uselessness of the humanities, her book ends up merely advertising marketing strategies for universities. Building on the techniques of business economics, the author attempts to conventionalize university as a business company. Aspects of educational and cognitive processes are conceptualized in a managerial-scientific framework and applied to university. The author concludes that concepts of marketing have so far been applied in the humanities only implicitly. While natural sciences as well as humanities both consist of applied research and basic research, the commercial viability of the humanities is probably inhibited by the concentration on the latter, which complicates mediation and strategic communication outside the academy. Stating a communicative demand of humanities in light of economic forces, Gülzow advocates an understanding of dialogical exchange processes by using concepts of commerce and social marketing as well as marketing strategies adapted to the academy to guide all university members.